Новые виды клещей-фитосейид фауны СССР (Parasitiformes, Phytoseiidae) - Колодочка, Л.А. (Вестник зоологии, 1980)
Three new phytoseiid mites Typhloctonus runiacus sp. n., Paraseiulus porosus sp. n. and Typhlodromus klimenkoi sp. n. from Ukrainian and Kirghiz plants are described.